2009
DOI: 10.1111/j.1471-4159.2009.06268.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective mesenchymal stem cells are endowed with a potent antioxidant effect in vivo

Abstract: 1These authors contributed equally to this study.Abbreviations used: CAT, catalase; CM, conditioned medium; EAE, experimental autoimmune encephalomyelitis; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; GFAP, glial fibrillary acid protein; GST, glutathione-S-transferase; MOG, myelin oligodendrocyte glycoprotein peptide; MS, multiple sclerosis; MSC, mesenchimal stem cell; MT, metallothionein; NeuN, neuronal nuclei; PARP-1, poly(ADP-ribose) polymerase-1; PBS, phosphate-buffered saline; RPMI, Royal Park Memoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 55 publications
4
118
1
4
Order By: Relevance
“…Animals were sacrificed at d 125 ± 2, and glutathione S-transferase (GST) activity in spinal cord was measured as previously reported (18). Aliquots of pooled spinal cord samples from each experimental group were homogenized in 10 volumes (w/v) of ice-cold PBS (50 mmol/L, pH 7.8) and centrifuged at 700g for 5 min at 4°C.…”
Section: Determination Of Glutathione S-transferase Activitymentioning
confidence: 99%
“…Animals were sacrificed at d 125 ± 2, and glutathione S-transferase (GST) activity in spinal cord was measured as previously reported (18). Aliquots of pooled spinal cord samples from each experimental group were homogenized in 10 volumes (w/v) of ice-cold PBS (50 mmol/L, pH 7.8) and centrifuged at 700g for 5 min at 4°C.…”
Section: Determination Of Glutathione S-transferase Activitymentioning
confidence: 99%
“…MSCs exert their effects through their antioxidant properties. MSCs exhibited antioxidant activity through the effect on the levels of glutathione, and superoxide dismutase, and modulating the pathways of antioxidant-related protein activation [19,20]. Furthermore, Kim et al [21] suggested that early intravenous injection of MSCs after acute spinal cord injury may prevent further damage through enhancement of antioxidative mechanisms, without inducing adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed MSC regulate effector functions of cells of the adaptive and innate immunity through the release of soluble factors such as prostaglandin E2 (PGE2), nitric oxide (NO), indoleamine 2,3-dioxygenase (IDO), and others [7] leading to the induction of peripheral tolerance [8]. Moreover, MSC can protect axons and improve neuronal survival [4,9,10] releasing antiapoptotic [11] or antioxidant molecules [12]. It has been also reported that MSC may foster endogenous neurogenesis [13] and oligodendrogenesis [14][15][16] not only by direct release of trophic factors but also by stimulating glial cells to secrete molecules leading to neuron survival and proliferation of the endogenous neural precursor cells [17].…”
Section: Introductionmentioning
confidence: 99%